Business-to-Business Value Co-creation: Suppliers' Perspective of Essential Information Systems Capabilities. (May 2023) - Sore, Sariseelia; Saunila, Minna; Ukko, Juhani; Helkkula, Anu
We focus on the digital solution supplier's perspective to analyse which information systems (IS) capabilities are essential for business-to-business (B2B) value co-creation. To gain a deeper understanding of the issue, a qualitative multi-case study was used. The results show that the focus of digital solutions in business has changed and shifted from the technical functions of solutions to the need for supplier and customer to work towards a common goal. The study proposes that, in advanced digital solutions, all parts of the solution development process require co-creation, either direct or indirect. In particular, forming IS–business partnerships, one of the spanning capabilities which integrates with internal organizational processes shows great potential in value co-creation. Originality builds on the understanding of which IS capabilities are essential when advanced digital solution suppliers offer services to their customers in the B2B context. This outcome contributes to the IS capabilities literature by showing the shift in focus from technically oriented capabilities to relationship-oriented capabilities in value co-creation.